Development of shear strength prediction model for RC beams strengthened with FRP strips based on a novel ensemble learning model - Huynh P. Nam; Nguyen D. D. Nam; Nguyen H. Thinh; Phan H. Nam; Ho M. Hung; Do V. Hai; Phan D. Thao (Tạp chí Khoa học và Công nghệ, 2024)
The use of fiber-reinforced polymer (FRP) strips as an external strengthening method has gained widespread acceptance for enhancing the capacity of aging reinforced concrete (RC) beams. Despite extensive research and practical applications, there exist unresolved issues necessitating further investigation, including interface bonding, failure mechanisms, and the development of accurate predictive models for shear strength, considering diverse parameters. This paper systematically reviews shear strength formulas applied in the strengthening of RC beams using FRP strips. An extensive experimental dataset is compiled from diverse sources to support the analysis.  Utilizing this dataset, a novel ensemble learning model is developed for predicting the shear strength contributed by FRP strips. Following the training of this model, the important score of each input parameter is also assessed. The findings presented herein contribute to a deeper understanding of the strengthening effectiveness of FRP strips on RC beams.